2015 International Conference on Industrial Engineering and Systems Management (IESM) 2015
DOI: 10.1109/iesm.2015.7380181
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Partial Information Sharing in Supply Chain dynamics

Abstract: Abstract-This paper provides an assessment of partial Information Sharing (IS) in Supply Chain (SC). We study the dynamics of collaborative multi-echelon structure, characterized by an increasing level of information visibility among partners. To do so, we mathematically model six four-echelon serial SCs via difference equations and conduct numerical simulations on the basis of a robust design of experiment. Results shows how (1) as the extent of IS increases, the performance of whole SC improves as well, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…It is found that the key problem of supply chain collaboration at this stage is the bullwhip effect caused by the inability to share information, which leads to the failure of supply chain enterprises to achieve global optimisation. This problem is not specific to a particular type of supply chain, it is very general [3,4]. Therefore, in order to realise the collaborative optimisation of the supply chain, information collaboration is the most important to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the key problem of supply chain collaboration at this stage is the bullwhip effect caused by the inability to share information, which leads to the failure of supply chain enterprises to achieve global optimisation. This problem is not specific to a particular type of supply chain, it is very general [3,4]. Therefore, in order to realise the collaborative optimisation of the supply chain, information collaboration is the most important to achieve.…”
Section: Introductionmentioning
confidence: 99%